Corporate Governance Determinants of Environmental and Climate Change Disclosures and Performance: An Australian Empirical Study - Chua, Pih Fong (Curtin University, 2018)
This study examines the association between corporate governance and environmental and climate-change (ECC) disclosures and performance of top ASX listed firms, during the operative periods of carbon pricing and prescriptive requirements on firms to disclose ECC information in corporate reports: 2011 to 2015. Quantitative evidence show board independence, environmental assurance, and boards with community affiliation are substantive measures while environmental committees and boards with environmental and social affiliations tend to be symbolic environmental governance measures.